DIAGNOSIS OF BENEFITS OF FIEP INTERNATIONAL PHYSICAL EDUCATION CONGRESS IN THE CITY OF FOZ DO IGUASSU - PR - 2014 (Fiep Bulletin - online, 2015)
The aim of this study was to measure the economic benefits brought to the city of Foz do Iguassu, during the organization of the FIEP International Physical Education Congress, which is held for 29 years. The total population taking part on the event was of 2897 congressmen, and the study was held with a sample of 239 individuals (57% of males, and 43% of females), with average ages between 20 and 29 years-old, coming up to 45.2% o the total population of the congress, which represents a sample with 94% of confidence, and 6% of error (BARBETTA, 2005, p. 59). The study identified an investment equivalent to U$ 7.5 million by the congressmen, which was injected into the city's economy directly at an average ticket of R$ 303.65, by mapping the participation of visitors in activities outside the congress. It was also identified that most of the congressmen are Brazilian, from Paraná state, accommodated in the congress partnership hotels, and use as their main transport coaches, and secondly by planes.
Keywords: Events; Economic benefits; FIEP Congress